The lactylation modification of proteins plays a critical role in tumor progression - Yi, Dehao; Zhou, Ke; Pan, Yinlong; Cai, Huazhong; Huang, Pan (Frontiers in Oncology, 2025)
Lactylation modifications have been shown to be a novel type of protein post-translational modifications (PTMs), providing a new perspective for understanding the interaction between cellular metabolic reprogramming and epigenetic regulation. Studies have shown that lactylation plays an important role in the occurrence, development, angiogenesis, invasion and metastasis of tumors. It can not only regulate the phenotypic expression and functional polarization of immune cells, but also participate in the formation of tumor drug resistance through a variety of molecular mechanisms. In this review, we review the latest research progress of lactylation modification in tumors, focusing on its mechanism of action in angiogenesis, immune cell regulation in tumor microenvironment (TME), and tumor drug resistance, aiming to provide a theoretical basis and research ideas for the discovery of new therapeutic targets and methods. Through the in-depth analysis of lactylation modification, it is expected to open up a new research direction for tumor treatment and provide potential strategies for overcoming tumor drug resistance and improving clinical efficacy.